Internet-delivered Acceptance and Commitment Therapy for Cancer Patients and Survivors: A Systematic Review - Francisco García-Torres; Margarita García-Carmona; Eliana Moreno; Francisco Jurado-González; Ángel Aguilera-Martín (SAGE Open)
Acceptance and commitment therapy (ACT) has proven effective in cancer patients, reducing common psychological symptoms and improving wellbeing. Moreover, the use of eHealth technologies makes support cheaper and easier to provide. The aim of this systematic review was to collect results on the effectiveness of internet-delivered ACT for common symptoms in cancer patients and survivors. The review follows PRISMA guidance and was registered in PROSPERO (CRD42022326543). Searches were conducted using PubMed, Web of Science, Scopus, EBSCOhost, and different web platforms of grey literature. Interventional studies were selected which focused on cancer patients and survivors, were published in English or Spanish, included at least two of the six main ACT components, and were partially or fully delivered through the Internet. The risk of bias was assessed following Cochrane’s recommendations. Eleven records from seven studies met the inclusion criteria. Only one study showed significant reductions in anxiety (reliable change index, RCI ∈ [2.32, 3.47]) and depression ( RCI ∈ [2.00, 4.00]). As regards quality of life, significant improvements were observed in certain domains such as cancer-related quality of life ( RCI  = 2.43), fatigue ( d  = −0.33), sleep problems ( d  = −0.53), physical and functional wellbeing (η 2 p  = .06), and participation in social activities ( d  = 0.18). ACT processes resulted in significant post-intervention improvements with regard to mindfulness ability and psychological flexibility. Results look promising; however, we believe that limitations such as blinding issues, the heterogeneity of designs and measurement tools, or the use of monetary incentives should be taken into account in future research.